Environmental education as a conservation strategy for the Orange-fronted Parakeet (Eupsittula canicularis) in the Central Pacific, Mexico - De Labra-Hernández, Miguel Ángel (2025)
Introduction: The implementation of environmental education as a conservation strategy for birds is a key element in the preservation of biodiversity. In Mexico, the Orange-fronted Parakeet (Eupsittula canicularis) is endangered due to habitat loss and poaching. Objective: The aim of the study was to raise environmental awareness among students (n = 52) from two primary schools through environmental education activities on the ecological importance of conserving the Orange-fronted Parakeet. Methodology: From September to November 2022, environmental education workshops were implemented for primary school students in two locations on the coastal plain of Oaxaca. The activities were divided into three stages: The three fundamental components of the programme are as follows: firstly, the dissemination of information; secondly, the provision of training; and thirdly, the promotion of awareness. Furthermore, a 5-item questionnaire was administered, and the responses of the students were compared prior to and following the environmental education workshops. Conclusions: It was demonstrated that the knowledge of the habitat, diet and reproduction of the Orange-fronted Parakeet among students was successfully improved. It has been demonstrated that dynamic activities, such as games, are more popular among students.